Buddhism and empire : the political and religious culture of early Tibet - Walter, Michael L. (Brill's Tibetan studies library, 2009)
This book analyzes the religious-political culture of the Tibetan Empire (c. 620-842) and the establishment of Buddhism, based on early sources. It shows how relationships formed in the Imperial period underlie many of the unique characteristics of traditional Tibetan Buddhism.